Rationale and design of a registry-based randomized controlled study of personalized biomarker-based risk score-guided stroke prevention treatment in atrial fibrillation - Hijazi, Ziad; Wallentin, Lars; Arheden, Håkan; Björkenheim, Anna; Frykman, Viveka; Janzon, Magnus; Ravn-Fischer, Annica; Renlund, Henrik; Själander, Anders; Åkerfeldt, Torbjörn; Oldgren, Jonas (American Heart Journal, 2025)
Background: Stroke and reduced survival are devastating complications of atrial fibrillation (AF). Biomarker-based ABC-AF risk scores improve risk prediction in AF, and risk-guided treatment recommendations may improve patient outcomes. Design: The ABC-AF study is a national, multicenter, prospective, registry-based, randomized controlled, parallel-group, open-label study. Its primary objective is to evaluate whether ABC-AF risk score-guided treatment recommendations improve outcomes in patients with AF. Consenting patients with AF registered in the Swedish national quality register for AF, AURICULA AF, will be randomized in a 1:1 ratio to either ABC-AF risk score-guided treatment recommendations or standard care. For participants in the active arm, investigators will receive a visual presentation of stroke and bleeding risks along with recommendations regarding the choice of oral anticoagulant (OAC) and additional treatments for stroke and bleeding prevention. In the control arm, patients are managed at the discretion of the investigator. Outcomes: The primary outcome is a composite of stroke or death. Secondary outcomes include the composite of stroke, death, and major bleeding, and the individual components of the primary outcome, myocardial infarction, and hospitalization for heart failure; and a safety endpoint of major bleeding. Study enrollment commenced on October 25, 2018, and terminated on May 12, 2023, after 3,933 patients had been recruited. Study results are expected in 2025. The ABC-AF study evaluates whether a personalized treatment recommendation strategy—guided by the biomarker-based ABC-AF risk score decision support— improves outcomes in AF.